2022
DOI: 10.1145/3550454.3555462
|View full text |Cite
|
Sign up to set email alerts
|

Sculptor

Abstract: Recent years have seen growing interest in 3D human face modeling due to its wide applications in digital human, character generation and animation. Existing approaches overwhelmingly emphasized on modeling the exterior shapes, textures and skin properties of faces, ignoring the inherent correlation between inner skeletal structures and appearance. In this paper, we present SCULPTOR, 3D face creations with Skeleton Consistency Using a Learned Parametric facial generaTOR , aiming to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Additionally, the landmark reduction ranged from 0.2 mm to 2.4 mm. Qiu et al [23] reported an improvement in the reconstruction result using CBCT data, with a facial MSE of approximately 1.5mm, but the result had poor extrapolation performance, with an error of 2.68mm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the landmark reduction ranged from 0.2 mm to 2.4 mm. Qiu et al [23] reported an improvement in the reconstruction result using CBCT data, with a facial MSE of approximately 1.5mm, but the result had poor extrapolation performance, with an error of 2.68mm.…”
Section: Discussionmentioning
confidence: 99%
“…This formulation was later adapted by Chandran et al [10] for facial performance retargeting. Qiu et al proposed SCULPTOR [37], a multi-identity joint morphable model of facial anatomy and skin learned from a database of computed tomography (CT) scans. Recently Choi et al proposed Animatomy [15], a muscle fiber based anatomical basis for animator friendly face modeling applications.…”
Section: Related Workmentioning
confidence: 99%
“…Since this structure does not exist in reality and is, therefore, not available for supervised learning, we formulate a learning framework where such rigidly deforming surface can be learnt only from the sparse set of anatomic constraints that can be computed between the skin and the underlying bones. As we will see in Section 5, learning this anatomic surface from data leads to several interesting applications in shape manipulation and performance retargeting that were previously challenging to obtain without expensive physical simulation [48] or extensive volumetric data capture [37].…”
Section: Anatomical Model Formulationmentioning
confidence: 99%